A STUDY TO EXPLORE THE SENSE OF IDENTITY AND BELONGINGNESS OF THE CHARACTER IN JHUMPA LAHIRI’S THE NAMESAKE - Sharma , Dinesh Kumar (International Journal of Psychosocial Rehabilitation, 2020)
JhumpaLahiri’s second abstract commitment, The Namesake, distributed in 2003, is a novel on the Indian diaspora. Indian history of diaspora is a long one, yet after freedom, it has grabbed the eye of imaginative journalists. The clever records the regular daily existence of an Indian pilgrim family that went to America after autonomy. It will overall be recognized that as a pilgrim’s young woman, the writer knows about the issues of pariahs living in America, especially their standards, values, culture, religion, language, or even more all, their personality. This paper is an analysis of the study to explore the sense of identity and belongingness of the character in JhumpaLahiri’s The Namesake.There are three sorts of alienation, alienation from oneself, alienation from others and alienation from the world in which one lives and these three types of alienation are interrelated. It is the interaction by which individuals become outsider to the world they are living in. Present day man doesn’t feel feeling of having a place with any individual or society or country since he needs to reside in separation and impact of cash power. He imagines that he can live alone on the planet without being connected to any individual. Now and again he chooses to look regarding his self-identity. He needs to stay isolates however arrives at acknowledge toward the end that there can be no getting away from life and its sufferings. To live cheerfully he should include himself with other people. He should play out his activities with no cravings. At the point when he understands this reality then he feels feeling of having a place and genuine importance of life. Whenever a man leaves his nation and goes to one more country for better open doors then he feels himself a more unusual there. He needs to interface himself to that spot yet his previous relations and customs generally overwhelms him there. Be that as it may, in the wake of expenditure numerous years in one more nation when he returns to his own country then he feels having a place with individuals and country.